How Should Lungs Be Allocated for Transplant? - Egan, Thomas M. (Seminars in Respiratory and Critical Care Medicine, 2018)
As lung transplantation became established therapy for end-stage lung disease, there were not nearly enough suitable lungs from brain-dead organ donors to meet the need, leading to a focus on how lungs are allocated for transplant. Originally lungs were allocated by the United Network for Organ Sharing (UNOS) like hearts—by waiting time, first to listed recipients in the organ procurement organization of the donor, then to potential recipients in concentric 500 nautical mile circles. This resulted in long waiting times and increasing waitlist deaths. In 1999, the Health Resources and Services Administration published a Final Rule, requesting UNOS to review organ allocation algorithms to ensure that they complied with the desire to allocate organs based on urgency, avoiding futile transplants, and minimizing the role of waiting time in organ allocation. This led to development of the lung allocation score (LAS), which allocates lungs based on urgency and transplant benefit, introduced in 2005. The U.S. LAS system was adopted by Eurotransplant to allocate unused lungs between donor countries, and by both Germany and the Netherlands for lung allocation in their countries. This article will review the history of lung allocation, discuss the impact of LAS and its shortcomings, suggest recommendations to increase the number of lungs for transplant, and improve allocation of donated lungs. Ultimately, the goal of organ transplant research is to have so many organs to transplant that allocation systems are unnecessary.
Keywords: lung transplant; lung allocation; lung allocation score; geography; lung waitlist